Special topics issue: "Complexity in the microcirculation". (16th May 2019) - Frisbee, Jefferson C.
Abstract: This Special Topics Issue of the journal "Microcirculation" presents seven manuscripts spanning multiple perspectives of investigation. The first two manuscripts present technical/analytical approaches to determining and quantifying vascular network structure, and the third presents a methodology for determining intravascular hemodynamics within the in situ microvascular network. The fourth manuscript utilizes complexity analyses to determine changes in microvascular perfusion as a predictor of disease severity, while the fifth study links the changes to perfusion complexity to tissue metabolic demand and potential limitations on mitochondrial metabolism within skeletal muscle. The sixth manuscript further addresses this critical topic, providing a state‐of‐the‐art discussion of skeletal muscle oxygen kinetics and the factors that impact this vital process. The final manuscript outlines the impact of the deletion of Robo4 on the vascular endothelium on microvascular function in white adipose tissue and the potentially beneficial effects for anti‐obesity treatment. We hope that this presentation of issues of "Complexity in the Microcirculation" will be beneficial to the reader.